ANALISIS PENGGUNAAN LISTRIK ARUS SEARAH UNTUK MENINGKATKAN LAJU PRODUKSI MINYAK BUMI JENIS MINYAK BERAT - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
rom EEOR, Electro Enhanced Oil Recovery, and a developing technology application which has been established earlier. The difference is ESOR relatively does not improve recovery factor of producing well. Ideally any crude oil producing well will be experiencing pressure decline which may affect crude oil production decrement, naturally. Regarding some similar researches around the world, the use of direct current electrical exposure was proven to increase number of heavy crude oil production. At least salinity, hydrocarbon chemical compounds and crude oil flow in the reservoir (electro-osmosis) involves during chemical processes in the reservoir while ESOR application. Number of electrons conducted from direct current electrical power supply will be a supporting media during chemical process of these parameters. Unfortunately after completing ESOR application in Lapangan X, the result was contradictive with this research hypothesis. Exposure of direct current electrical supply did not increased heavy crude oil production. On a contrary, parameter of salinity and API gravity as produced heavy crude oil quality, were improving significantly.